HBimmCue: A Versatile Fluorescent Probe for Multi‐Scale Imaging of Lipid Polarity and Membrane Order in Inner Mitochondrial Membrane - Shu Gao; Jing Sun; Yiwei Hou; Xichuan Ge; Ming Shi; Hongxi Zheng; Yan Zhang; Meiqi Li; Baoxiang Gao; Peng Xi (Advanced Science)
Abstract Mitochondrial membrane environmental dynamics are crucial for understanding function, yet high‐resolution observation remains challenging. Here, HBimmCue is introduced as a fluorescent probe localized to inner mitochondrial membrane (IMM) that reports lipid polarity and membrane order changes, which correlate with cellular respiration levels. Using HBimmCue and fluorescence lifetime imaging microscopy (FLIM), IMM lipid heterogeneity is uncovered across scales, from nanoscale structures within individual mitochondria to mouse pre‐implantation embryos. At the sub‐organelle level, stimulated emission depletion (STED)‐FLIM imaging highlights nanoscale polarity variations within the IMM. At the sub‐cellular and cellular level, reduced IMM lipid polarity is observed in damaged mitochondria marked for lysosomal degradation and distinct IMM lipid distributions are identified in neurons and disease models. Additionally, metabolic dysfunction associated with oocytes aging and metabolic reprogramming from zygote to blastocyst is detected. Together, the work demonstrates the broad applicability of HBimmCue, offering a new paradigm for investigating lipid polarity and respiration level at multiple scales.